Electroluminescence powdered ZnS:Cu obtained by one-stage synthesis - Bacherikov, Yu.Yu.; Zhuk, A.G.; Okhrimenko, O.B.; Kardashov, D.L.; Kozitskiy, S.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
Photo- and electroluminescence properties of ZnS obtained using selfpropagating high-temperature synthesis and doped with Cu were studied in this work. It has been shown that high-temperature one-stage synthesis enables to obtain two-phase system ZnS-Cu₂₋xS with the maximum radiation 515 nm for photo- and electroluminescence. Since the synthesis process is non-equilibrium, impurities distribute nonuniformly in the bulk of microcrystals. Additional annealing and introducing the Ga coactivator lead to more non-uniform distribution of impurities in the bulk of microcrystals. It causes the increase in the intensity of the blue band in photoluminescence spectra and shift of the maximum of electroluminescence toward longer wavelengths. It is probable that this increase in the intensity of the blue band in photoluminescence spectra is caused by formation of the radiative centers Cui₋CuZn.